Variable Nuclearity in Lanthanoid Coordination Chemistry. Issue 17 (6th May 2014) - Andrews, Philip C.; Hennersdorf, Felix; Junk, Peter C.; Thielemann, Dominique T.
Abstract: A series of lanthanoid and iodine containing compounds of formulae [Ln(IPhacac)3 (dmf)2 ], [K(dmf)2 {Ln(IPhacac)4 }] n and [Ln5 (OH)5 (IPhacac)10 ] {(IPhacac) = bis( para ‐iododibenzoyl)methanide} have been prepared and structurally characterised. X‐ray crystallography establishes that the compounds exist as monomers [Ln(IPhacac)3 (dmf)2 ] {Ln = Pr (1 ), Nd (2 ), Tb (5 ), Dy (6 )} and [Yb(IPhacac)3 (dmf)2 ][Yb(IPhacac)3 (dmf)(H2 O)] (7 ) (dmf = N, N ‐dimethylformamide), polymers [K(dmf)2 {Ln(IPhacac)4 }] n {Ln = Nd (2a ), Eu (3a ), Gd (4a ), Tb (5a ), Dy (6a )} and pentanuclear clusters [Ln5 (OH)5 (IPhacac)10 ] {Ln = Tb (5b ), Dy (6b ), Yb (7b )}. Abstract : A series of lanthanoid and iodine containing monomeric, polymeric and cluster compounds of formulae [Ln(IPhacac)3 (dmf)2 ], [K(dmf)2 {Ln(IPhacac)4 }]n and [Ln5 (OH)5 (IPhacac)10 ] have been prepared.